2019
DOI: 10.21070/jees.v4i1.1948
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Perception on Academic Reading Log for Essay Writing Literacy: Some Influential Points

Abstract: Reading log or the so-called reading journal is a journal to monitor how far the students read within their own pace and time. This study aimed at investigating some influential points of using reading log in order to enhance the students’ ability in writing academic article. The participants of this study were twenty sophomores pursuing their study at Universitas Islam Malang taking Writing IV class. They were asked to fill reading logs given after reading academic articles. They had to read one academic arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In EFL classes, reading and writing interplayed. It is in line with Rahmawati (2019), who states that the reading and writing should not be seen as being in opposition in which the more the learners are exposed to the reading activities, the more the learners are able to write in such a way. In writing, students are demanded to produce and compose some academic or non-academic outputs as their writing products.…”
Section: Introductionsupporting
confidence: 76%
“…In EFL classes, reading and writing interplayed. It is in line with Rahmawati (2019), who states that the reading and writing should not be seen as being in opposition in which the more the learners are exposed to the reading activities, the more the learners are able to write in such a way. In writing, students are demanded to produce and compose some academic or non-academic outputs as their writing products.…”
Section: Introductionsupporting
confidence: 76%
“…The second study held by Mbato (2019) discovered that students possessed some degree of critical thinking in reading, but to become critical, they had to be in a learning atmosphere where their critical thinking in reading could be nurtured consistently and intensively. Then, the study by Rahmawati & Sholihah (2019) revealed that reading logs is very beneficial for the students specifically when they were reading academic articles. Furthermore, Setiawan & Ena (2019) in their study showed that students have positive selfefficacy expectations about their reading, especially in terms of describing, summarizing, and comprehending graphics found in the text without the help of their teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Having reviewed these previous studies, the researchers observed that the emphasis they made was heavily on external supporting factors of academic reading development, such as problem-solving strategies in online reading (Sari & Ningsih, 2020), the role of the reading log (Rahmawati, 2019), and critical thinking atmosphere (Mbato, 2019). Only two research studies (Setiawan &Ena, 2019 andYou, Dang &Lim, 2016) highlighted the influence of selfefficacy in academic performances, including reading, however, the sources of self-efficacy were found in different indications, such as their mastery experiences, vicarious experiences, verbal persuasion, and emotional and psychological states.…”
Section: Introductionmentioning
confidence: 99%
“…Many students found difficulties in writing. Students have difficultes in writing because they have limited vocabulary (Indrasari et al, 2018), difficulty in building up the idea (Du & List, 2020), difficulty in producing a language (Teng & Zhang, 2016), they did not have mastery in grammar (Rahmawati, 2019), and they were not interested in writing (Xiao, 2007).…”
Section: Introductionmentioning
confidence: 99%